Regulating the Solvation Structure of Electrolyte via Dual–Salt Combination for Stable Potassium Metal Batteries - Jimin Park; Gwangeon Oh; Un‐Hyuck Kim; Muhammad Hilmy Alfaruqi; Xieyu Xu; Yangyang Liu; Shizhao Xiong; Adi Tiara Zikri; Yang‐Kook Sun; Jaekook Kim; Jang‐Yeon Hwang (Advanced Science, 2023)
Abstract Batteries using potassium metal (K‐metal) anode are considered a new type of low‐cost and high‐energy storage device. However, the thermodynamic instability of the K‐metal anode in organic electrolyte solutions causes uncontrolled dendritic growth and parasitic reactions, leading to rapid capacity loss and low Coulombic efficiency of K‐metal batteries. Herein, an advanced electrolyte comprising 1 M potassium bis(fluorosulfonyl)imide (KFSI) + 0.05 M potassium hexafluorophosphate (KPF6) dissolved in dimethoxyethane (DME) is introduced as a simple and effective strategy of regulated solvation chemistry, showing an enhanced interfacial stability of the K‐metal anode. Incorporating 0.05 M KPF6 into the 1 M KFSI in DME electrolyte solution decreases the number of solvent molecules surrounding the K ion and simultaneously leads to facile K+ de‐solvation. During the electrodeposition process, these unique features can lower the exchange current density between the electrolyte and K‐metal anode, thereby improving the uniformity of K electrodeposition, as well as potentially suppressing dendritic growth. Even under a high current density of 4 mA cm−2, the K‐metal anode in 0.05 M KPF6‐containing electrolyte ensures high areal capacity and an unprecedented lifespan with stable Coulombic efficiency in both symmetrical half‐cells and full‐cells employing a sulfurized polyacrylonitrile cathode.